2023
DOI: 10.1093/aobpla/plad069
|View full text |Cite
|
Sign up to set email alerts
|

Tracking canopy chlorophyll fluorescence with a low-cost light emitting diode platform

Logan E G Brissette,
Christopher Y S Wong,
Devin P McHugh
et al.

Abstract: Chlorophyll fluorescence measured at the leaf scale through pulse-amplitude modulation (PAM) has provided valuable insight into photosynthesis. At the canopy- and satellite-scale, solar-induced fluorescence (SIF) provides a method to estimate the photosynthetic activity of plants across spatiotemporal scales. However, retrieving SIF signal remotely requires instruments with high spectral resolution, making it difficult and often expensive to measure canopy-level steady-state chlorophyll fluorescence under natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 77 publications
1
2
3
Order By: Relevance
“…This is in contrast to Brissette et al. (2023), who found close correspondence between the photodiode and hyperspectral derived LEDIF values. This is likely due to lower signal‐to‐noise ratio for the photodiode sensors (low intensity ∼0.01 μmol m −2 s −1 signal and ∼2.5 signal‐to‐noise ratio; Figure 2), which they were placed further away from the canopy in a less controlled environment as was done in the experiment by Brissette et al.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This is in contrast to Brissette et al. (2023), who found close correspondence between the photodiode and hyperspectral derived LEDIF values. This is likely due to lower signal‐to‐noise ratio for the photodiode sensors (low intensity ∼0.01 μmol m −2 s −1 signal and ∼2.5 signal‐to‐noise ratio; Figure 2), which they were placed further away from the canopy in a less controlled environment as was done in the experiment by Brissette et al.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to Brissette et al (2023), who found close correspondence between the photodiode and hyperspectral derived LEDIF values. This is likely due to lower signal-to-noise ratio for the photodiode sensors (low intensity ∼0.01 μmol m −2 s −1 signal and ∼2.5 signal-to-noise ratio; Figure 2), which they were placed further away from the canopy in a less controlled environment as was done in the experiment by Brissette et al (2023) (∼0.05 μmol m −2 s −1 signal). For the hyperspectral sensor, we manually set a 0.6 s integration time to maximize signal-to-noise ratio while avoiding saturation (low intensity ∼2.5 signal-to-noise ratio Figure 2).…”
Section: Ledif Retrievalcontrasting
confidence: 99%
See 3 more Smart Citations